2017
DOI: 10.1002/cbin.10723
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐195‐5p suppresses osteosarcoma cell proliferation and invasion by suppressing naked cuticle homolog 1

Abstract: MiR-195-5p has been shown to play an essential role in human cancer progression. Nevertheless, the biological role of miR-195-5p in osteosarcoma development remains unclear. In this study, real-time PCR was performed to examine the miR-195-5p expression in human osteosarcoma cell lines. CCK-8 assay and Transwell assay were carried out to measure the effect of miR-195-5p on cell proliferation and invasion. Luciferase reporter assay was used to identify the targets of miR-195-5p. The results showed that miR-195-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…Studies have reported that miR‐195‐5p plays an important role in inhibiting the development of various human cancers, including bladder, cervical, and breast cancers . MiR‐195‐5p can suppress OS cell metastasis by targeting CCND1 and can also suppress OS cell proliferation and invasion by suppressing naked cuticle homolog 1 . However, current studies have been unable to clarify the exact relationship between XIST and miR‐195‐5p.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have reported that miR‐195‐5p plays an important role in inhibiting the development of various human cancers, including bladder, cervical, and breast cancers . MiR‐195‐5p can suppress OS cell metastasis by targeting CCND1 and can also suppress OS cell proliferation and invasion by suppressing naked cuticle homolog 1 . However, current studies have been unable to clarify the exact relationship between XIST and miR‐195‐5p.…”
Section: Discussionmentioning
confidence: 91%
“…Another important miRNA identified in this study was over-expressed miR-34a-5p in MPE group which showed a malignant tendency in lesions. This statement was supported by some previous publications [22][23][24]. In non-small cell lung cancer, high-expression of miR-34a-5p can induce cell apoptosis by targeting MDM4, and increase p53 and p21 protein expressions [16].…”
Section: Discussionsupporting
confidence: 79%
“…Another target gene of miR-195-5p AGO4, as an microRNA machinery gene, was demonstrated to be upregulated in ovarian carcinogenesis and apoptosis process [15]. In addition, miR-195-5p has been widely identified as tumor suppressor in osteosarcoma, prostate cancer, and bladder cancer [4,7,23].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrantly expressed miRs are implicated in the regulation of OS onset and development (23)(24)(25). Therefore, key miRs in OS must be identified to develop promising and effective therapeutic targets for patients with OS.…”
Section: Discussionmentioning
confidence: 99%